Single cell trapping in microfluidic channel via hydrodynamic manipulation - Ahmad Khalili, Amelia (2013)
Microfluidic devices are important for the single cell analysis such as cell mechanical and electrical characterization. Single cell characterization could be related to many significant applications including early disease diagnosis. However to perform the single cell manipulation, firstly a single cell have to be isolated and a platform for the cell manipulation have to be provided. One of the methods to trap a single cell is by using hydrodynamic trapping in the microfluidic channel. This study provides a finite element model for single cell trapping for a yeast cell model. The objectives of the simulations are to obtain the appropriate channels’ geometry and optimized ratio of the fluid’s inlet and suction flow rate to trap a single yeast cell. Trap channel was designed to trap a 5 µm yeast cell with a suction hole placed in the end of the trap channel. Design geometry and ratio of fluid flow rates referring to the hydrodynamic concept were studied for the cell trapping model. The analysis was carried out using numerical solutions from the finite element ABAQUS-FEA software. Using the cell trapping model, a single yeast cell able to be trapped into the trap channel with optimized channel’s suction hole’s geometry and appropriate fluid’s inlet and suction flow rate ratio.